2021
DOI: 10.1186/s12938-021-00873-9
|View full text |Cite
|
Sign up to set email alerts
|

MXene in the lens of biomedical engineering: synthesis, applications and future outlook

Abstract: MXene is a recently emerged multifaceted two-dimensional (2D) material that is made up of surface-modified carbide, providing its flexibility and variable composition. They consist of layers of early transition metals (M), interleaved with n layers of carbon or nitrogen (denoted as X) and terminated with surface functional groups (denoted as Tx/Tz) with a general formula of Mn+1XnTx, where n = 1–3. In general, MXenes possess an exclusive combination of properties, which include, high electrical conductivity, g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
101
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 143 publications
(101 citation statements)
references
References 116 publications
0
101
0
Order By: Relevance
“… 21 23 Despite its utilization in different biomedical applications, the effect of incorporating MXene in bioprinted bioinks has been poorly explored. 24 In the literature, there is only one study conducted by Rastin et al in which MXene was incorporated in a hyaluronic acid/alginate hydrogel. The results of the study showed promising potential of MXene in 3D bioprinting.…”
Section: Introductionmentioning
confidence: 99%
“… 21 23 Despite its utilization in different biomedical applications, the effect of incorporating MXene in bioprinted bioinks has been poorly explored. 24 In the literature, there is only one study conducted by Rastin et al in which MXene was incorporated in a hyaluronic acid/alginate hydrogel. The results of the study showed promising potential of MXene in 3D bioprinting.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years MXenes have been used as novel photothermal therapy agents to treat mouse breast cancer cells due to their unique properties [40]. [39]. 2021, BMC); (b) MXene chemistry (Reprinted with permission from ref.…”
Section: Mula Mmentioning
confidence: 99%
“…It is being used as a solution for people who have allergic responses to CT contrast agents. Materials containing gadolinium, which are extensively employed as MRI contrast agents, have been linked to an increased risk of kidney injury [ 8 ]. As an MRI contrast agent, the composites made by growing nanosized manganese oxide on MXenes have shown great promise [ 79 ].…”
Section: Biomedical Applications Of Mxenesmentioning
confidence: 99%
“…Gogotsi’s group at Drexel university recently developed a vast family of transition metal nitrides and/or carbides, termed MXenes [ 3 ], which are also obtainable from other layered compounds, such as Zr 3 Al 3 C 5 and Mo 2 Ga 2 C. The common formula for MXenes can be transcribed as: M n+1 X n T x ( n = 1–3) [ 4 ], where M is an early transition metal (e.g., Zr, Ti, V, Ta, Nb, or Mo) and X is nitrogen and/or carbon [ 5 ]. Such MXenes are usually prepared from their corresponding mass in MAX phase by careful etching of layers of Group IIIA or IVA elements by fluoride-based entities, and therefore their basal faces are frequently finished with surface moieties (T x ), namely, a mixture of O, F and OH [ 6 , 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%